Gambaran Peran Ibu dalam Mengajari Toilet Training pada Anak Usia Toddler (18-24 Bulan) Sesudah Diberikan Pendidikan Kesehatan di Kelurahan Ketawanggede - maria goreti; Anis Kusnawati (Poltekkes Kemenkes Malang, 2019)
The stage of psychosexual development in toddler age is the anal phase which is the right time for toilet training. The role of mothers in toilet training for toddlers is very important, one of which is to provide health education. This study aims to determine the role of mothers in teaching toilet training in toddler age children 18-24 months after being given health education in Ketawanggede Village. This research is a descriptive case study with two subjects and was conducted in January 2019, using an interview sheet and an observation sheet. The results showed that the first subject experienced a change in role from less to sufficient, and the second subject underwent a change from less to good after being given health education. The ability of children in toilet training the first subject and the second subject changes from less to good after being taught toilet training. Recommendations for further research is that it is recommended that future researchers continue to carry out health education related to the role the subject has not carried out in order to be the same perception as researchers.